2010
DOI: 10.3892/or_00000808
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of MGMT promoter methylation in glioblastoma patients treated with temozolomide-based chemoradiation: A Portuguese multicentre study

Abstract: Abstract. Glioblastoma (GBM) is the most common and aggressive primary brain tumor. The identification of novel molecular prognostic markers of GBM has recently been an area of great interest in neuro-oncology. The methylation status of the MGMT gene promoter is currently a promising molecular prognostic marker, but some controversial data have precluded its clinical use. We analyzed MGMT methylation by methylation-specific PCR in 90 GBM patients from four Portuguese hospitals, uniformly treated with radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Twenty studies met the inclusion criteria for this metaanalysis, including a total of 2,018 patients (Table 1) [7,17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Two of these studies also reported subgroup analyses.…”
Section: Search Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Twenty studies met the inclusion criteria for this metaanalysis, including a total of 2,018 patients (Table 1) [7,17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Two of these studies also reported subgroup analyses.…”
Section: Search Resultsmentioning
confidence: 98%
“…If the 95% CI interval was not reported, it was calculated from the HR and associated P value [16]. For one study the authors sent us their raw data, and granted us permission to generate the HR and 95% CI [17].…”
Section: Data Abstractionmentioning
confidence: 99%
“…In contrast, other studies revealed that MGMT promoter methylation was not associated with better OS and progression-free survival; both endpoints were comparable in patients with expressed MGMT and those with MGMT silencing. The studies by Costa et al and Park et al on glioblastoma patients treated with TMZ-based chemoradiation revealed that MGMT promoter methylation was not associated with improved outcome [ 12 , 13 ]. Our study found that MGMT promoter methylation was not associated with a significant change in patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of MGMT promoter methylation with IDH1 mutation, treatment modalities and survival rates showed controversial results. Some studies revealed that glioblastomas with methylated MGMT promoter were more sensitive to chemotherapeutic agent (TMZ) resulting in a better survival rate [9][10][11], while other studies revealed that MGMT promoter methylation was not associated with better overall survival (OS) [12,13]. Combs et al also found a none-favourable OS in a group of 160 patients with glioblastoma treated with radiotherapy and TMZ.…”
Section: Introductionmentioning
confidence: 99%
“…Not only MGMT is a positive predictive factor for TMZ therapy (see Table 1 ), but also MGMT is a positive prognostic marker. Many studies have reported that MGMT methylation predicts longer OS [ 33 , 81 , 151 , 152 , 153 ]. Zhang et al conducted a meta-analysis of 15 studies reporting the effect of MGMT promoter methylation on OS by univariate analysis and 14 studies by multivariate analysis.…”
Section: Mgmtmentioning
confidence: 99%